Tourism Application Information System Security Audit Using Cobit 5 Framework on Palembang City - Febriyanti Panjaitan; Susan Dian Purnamasari; Windi Melisa (Universitas Bina Darma, 2022)
Information technology is important in organizations so that the goals and expectations of the objectives of implementing IT can be achieved. The tourism office of the city of Palembang is an institution that has used information technology to help the continuity of their work. The tourism office of the city of Palembang has not conducted an audit of improving the security of the existing information system. Therefore, to avoid events that do not require an information security system audit. Cobit 5 framework that can be used as a reference for information system governance to achieve the expected goals. This study only discusses the security management process which includes the DSS05 (Delivery, service, and security) domain by collecting data using a questionnaire. The value of the level of security improvement to be achieved in the security system should reach level 5 and can provide recommendations that will be followed up by the institution to make improvements in the future.